2014
DOI: 10.1002/ptr.5117
|View full text |Cite
|
Sign up to set email alerts
|

Barberry Treatment Reduces Serum Anti-Heat Shock Protein 27 and 60 Antibody Titres and High-sensitivity C-reactive Protein in Patients with Metabolic Syndrome: A Double-blind, Randomized Placebo-controlled Trial

Abstract: Metabolic syndrome is an important risk factor for cardiovascular disease (CVD). The heat shock proteins (HSPs) are associated with risk factors for CVD. The aim of the present study was to survey the effect of barberry on antibody titres to HSPs and high-sensitivity C-reactive protein (hs-CRP) in patients with metabolic syndrome. In our study, subjects (N=106, 79 women and 27 men, 18-65 years old) with metabolic syndrome were randomized into two groups: a group of patients who received three capsules of barbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…There is growing body of data suggesting the important role of this marker in CAD and stroke (12)(13)(16)(17)(18). In the present study, we also investigated its relationship with age.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…There is growing body of data suggesting the important role of this marker in CAD and stroke (12)(13)(16)(17)(18). In the present study, we also investigated its relationship with age.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…This study is one of the first studies to document the effects of flaxseed supplementation in ameliorating central obesity and MetS. In previous interventional studies, the beneficial effects of some dietary elements on MetS components have been shown (Akaberi and Hosseinzadeh, ; Yang et al ., ; Hosseini and Hosseinzadeh, ; Jeong et al ., ; Zilaee et al ., ; Razavi and Hosseinzadeh, ; Yang et al ., ); however, none of these dietary agents could affect all components of the MetS significantly. In this study, using flaxseed supplementation exacerbated the effect of a low intensive lifestyle modification, which can be adhered for a lifelong duration.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized double‐blind clinical trial in 106 subjects with metabolic syndrome, administration of three capsules of barberry (containing 200 mg of dried barberry) for 6 weeks significantly improved lipid profile and decreased anti‐HSPs 27 and 60 and hs‐CRP levels (Zilaee et al, ). Barberry supplementation also caused a significant reduction in pro‐oxidant–antioxidant balance in these patients (Mohammadi et al, ).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%